Implementation of an Automated Dispensing Cabinet Stewardship Program at a Tertiary Academic Medical Center. (December 2014) - Hussey, Aaron P.; Cook, Bryan M.; Quane, Adam D.; Sweet, Stephen R.; Szumita, Paul M.
Automated dispensing cabinet (ADC) use within hospitals is designed to replace or partially replace medication cabinets or carts to allow for a more decentralized model of medication distribution. This project was designed to improve medication delivery by decreasing the burden of dispensing patient-specific medications from a centralized inpatient pharmacy while decreasing overall inventory cost. This single-center pilot analysis evaluated ADC inventory optimization in a mixed medical population. Data collected included inventory cost on ADC, medications removed from or added to ADC, patient-specific medications sent from central pharmacy, and the rate of medication stock outs on ADC.